Prognostic significance of surfactant protein A, surfactant protein D, Clara cell protein 16, S100 protein, trefoil factor 3, and prostatic secretory protein 94 in idiopathic pulmonary fibrosis, sarcoidosis, and chronic pulmonary obstructive disease - Doubková, Martina; Karpíšek, Michal; Mazoch, Jiri; Skřičková, Jana; Doubek, Michael (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Identification of serum and bronchoalveolar lavage fluid (BALF) biomarkers may facilitate diagnosis and prognostication in various lung disorders. Objective: Serum and BALF levels of surfactant protein A (SP-A), surfactant protein D (SP-D), Clara cell protein 16 (CC16), S100 protein, trefoil factor 3 (TFF3), and prostatic secretory protein 94 (PSP94) were evaluated in 94 consecutive patients (idiopathic pulmonary fibrosis (IPF; n=18), sarcoidosis (n=25), chronic obstructive pulmonary disease (COPD; n=51)), and in 155 healthy controls. Methods: Biomarkers were measured at diagnosis and compared with disease characteristics. Both uniparametric and multiparametric analyses were used. Results: Seven significant correlations were found: 1) BALF PSP94 level correlated with prognosis of sarcoidosis (P=0.035); 2) BALF SP-D level with pulmonary functions in IPF (P=0.032); 3) BALF SP-D and TFF3 with IPF mortality (P=0.049 and 0.017, respectively); 4) serum TFF3 level with COPD mortality (P=0.006,); 5) serum SP-A with pulmonary functions impairment in IPF (P=0.011); 6) serum SP-D level was associated with HRCT interstitial score in IPF (P=0.0346); and 7) serum SP-A was associated with staging of COPD according to spirometry (P<0.001). Moreover, our analysis showed that some biomarker levels differed significantly among the diseases: 1) BALF SP-D level differed between sarcoidosis and IPF; 2) serum SP-A level differed among IPF, sarcoidosis, COPD and was also different from healthy controls; 3) serum S100A6, S100A11 levels differed among IPF, sarcoidosis, COPD from healthy controls 4) serum SP-D, CC16, TFF-3 levels distinguished IPF patients from healthy controls; and 5) serum CC16, TFF3, PSP94 distinguished COPD patients from healthy controls. Our study shows that some of selected biomarkers should have prognostic value in the analysed lung disorders. On the other hand, these biomarkers do not appear to be unequivocally suitable for differential diagnosis of these disorders.